STRATEGY FOR HUMAN TALENT AND JOB SKILLS IN AN AGRO-INDUSTRIAL COMPANY - Jesús Daniel Morisaki Mego; Patricia del Rocío Chávarry Ysla; Francisco Pedro Morisaki Mego (Journal of Management and Business Education, 2020)
The present research aimed to determine how deficiencies in the management of administrative human talent influence the levels of development of labor competencies in an agro-industrial company, theoretically based on the process of development of human talent and its dynamics, at the same time it diagnosed the current state of the competences of administrative collaborators. The methodology was mixed, descriptive, using the survey with its structured questionnaire validated by Cronbach's alpha, whose population was made up of 40 administrative collaborators and the sample was 27. At the consolidated level, the attitude dimension reached an average mean of 2, 76, knowledge competence 2.46 and skill competence an average mean of 2.47. The results reveal that there are deficiencies in various competencies of human talent, which correspond to the three operationalized dimensions: attitude, knowledge, ability. It was concluded that the collaborators of the agroindustrial company presented deficiencies in their labor competencies in the 3 dimensions addressed, since a human talent development strategy is urgently needed to improve the levels of labor competencies in the collaborators.